Measuring the Financial Pulse: A Statistical Analysis of Working Capital and Insolvency Risk in 21st Century Manufacturing SMEs - Nuñez, Edison Roberto Valencia; Valencia, Christian Alberto López; Acaro, Yanela Stefany Quiroga; Reyes, Johanna Enith Aguilar; Calva, Miguel Ángel Guallpa; Ulloa, Diana E Vargas (Migration Letters, 2023)
This paper aims to investigate the analysis and relationship between working capital and the risk of corporate insolvency. It adopts a quantitative approach and is based on the review of the statements of financial position presented in the SUPERCIAS database, covering a set of 112 SMEs that have maintained their constancy during the period 2017 to 2020. Data collection was carried out from secondary sources, using an observation sheet as a means of recording. Various statistical techniques were applied in the analysis, including a descriptive analysis and Spearman’s Rho correlation, in addition, Ecotrim software was used to predict into the future over a period of 12 quarterly observations (3 years) and also time series through the ARIMA model, which facilitated the construction and development of four ARIMA projection models of the two variables as a function of size to obtain a better time series model such as SARIMA in order to identify the most appropriate size and year to make future predictions with greater accuracy. The results reflected how companies by size (small and medium) experienced changes throughout the study period. In addition, in the years 2019 and 2020, the working capital and insolvency risk variables were impacted due to the pandemic in this sector, resulting in a deterioration of their values. Both working capital and insolvency risk showed a moderately negative correlation. It was also concluded that medium-sized companies are the most suitable for forecasting.